Compression-only life support (COLS) for cardiopulmonary resuscitation by layperson outside the hospital - Syed Moied Ahmed; Rakesh Garg; Jigeeshu Vasishtha Divatia; SSC Chakra Rao; Bibhuti Bhusan Mishra; M Venkatagiri Kalandoor; Mukul Chandra Kapoor; Baljit Singh (Indian Journal of Anaesthesia, 2017)
The cardiopulmonary resuscitation (CPR) guidelines of compression-only life support (COLS) for management of the victim with cardiopulmonary arrest in adults provide a stepwise algorithmic approach for optimal outcome of the victim outside the hospital by untrained laypersons. These guidelines have been developed to recommend practical, uniform and acceptable resuscitation algorithms across India. As resuscitation data of the Indian population are inadequate, these guidelines have been based on international literature. The guidelines have been recommended after discussion among Indian experts and the recommendations modified to ensure its practical applicability across the country. The COLS emphasises on early recognition of cardiac arrest and activation, early chest compression and early transfer to medical facility. The guidelines emphasise avoidance of any interruption of chest compression, and thus relies primarily on chest compression-only CPR by laypersons.